The rural homeless in Bangladesh - Rahman, Tahmeena (Dhaka : UNICEF, 1993)
Study restricted to four districts of Bangladesh and was conducted in 1987 and updated to 1991.
Includes index and bibliographical references
Keywords: Rural homeless person -- Bangladesh; Rural poor -- Bangladesh